Birthweight and the Risk of Atopic Diseases: The Isaac Phase Iii Study - Mallol-Villablanca, E (Blackwell Publishing Ltd, 2014)
Background: The association between birthweight and asthma, eczema and rhinoconjunctivitis is conflicting. Aims: To examine the association between birthweight and symptoms of asthma, eczema and rhinoconjunctivitis. Methods: Parents or guardians of children aged 6-7 yr completed written questionnaires about symptoms of asthma, rhinoconjunctivitis and eczema, and several risk factors, including birthweight. Results: There were 162,324 children from 60 centres in 26 countries. Low birthweight (<2.5 kg) was associated with an increased risk of symptoms of asthma (current wheeze odds ratio = 1.20; 95% confidence interval = 1.12-1.30). Low birthweight was associated with a lower risk of eczema ever. Low birthweight was not associated with rhinoconjunctivitis. Large babies (birthweight ?4.5 kg) were not associated with any of these outcomes. Conclusions: This study has confirmed that low birthweight is a risk factor for symptoms of asthma, but not for rhinoconjunctivitis. The findings for eczema are equivocal. © 2014 John Wiley & Sons A/S. Published by John Wiley & Sons Ltd.